Women in Organized Crime - Pavićević, Olivera; Bulatović, Aleksandra (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
The social setting defines individual readiness to take certain social and entrepreneurial risks. Hence, power relations offer a view over dimensions of active and passive participation in organized crime as it is being reflected in the political and economic arena. Although gender relations have a different social profile and internal dynamics in different countries with different traditions of social management, statistical data on crime indicate involvement of women in organized crime to be a global phenomenon. The trans-ideological capacity of organized crime and the degree of transnational interconnectidness, significantly affect changes in gender relations within organized crime and generate new related dynamics. Gender boundaries transformation in the organized crime sphere places those boundaries in the space of their interconnection in socio-cultural processes in and out of organized crime as a phenomenon. In this article, the authors present the place and role of women in contemporary organized crime. The aim of the article is to highlight lines of influence and consequences of gender boundaries transformation within the framework of organized crime activities.